2016
DOI: 10.1038/srep26149
|View full text |Cite
|
Sign up to set email alerts
|

Fructose, but not glucose, impairs insulin signaling in the three major insulin-sensitive tissues

Abstract: Human studies support the relationship between high intake of fructose-sweetened beverages and type 2 diabetes, but there is a debate on whether this effect is fructose-specific or it is merely associated to an excessive caloric intake. Here we investigate the effects of 2 months’ supplementation to female rats of equicaloric 10% w/v fructose or glucose solutions on insulin sensitivity in target tissues. Fructose supplementation caused hepatic deposition of triglycerides and changed the fatty acid profile of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 52 publications
10
58
0
Order By: Relevance
“…Namely, hepatic fatty acid profile was characterized by a higher proportion of MUFA, lower proportion of PUFA and increased oleic/stearic acid ratio (Δ9 desaturase index), regardless of stress. These results are in accordance with other animal studies using high-fructose diet [39][40][41]. In addition, it was previously demonstrated that fructose-induced increase of MUFA and decrease of PUFA in the liver were not accompanied by lipid accumulation and hepatic steatosis [39,40], but rather with increased secretion of triglycerides, as observed in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Namely, hepatic fatty acid profile was characterized by a higher proportion of MUFA, lower proportion of PUFA and increased oleic/stearic acid ratio (Δ9 desaturase index), regardless of stress. These results are in accordance with other animal studies using high-fructose diet [39][40][41]. In addition, it was previously demonstrated that fructose-induced increase of MUFA and decrease of PUFA in the liver were not accompanied by lipid accumulation and hepatic steatosis [39,40], but rather with increased secretion of triglycerides, as observed in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Baena et al reported that fructose, but not glucose, exhibited adverse effects towards insulin signaling in white adipose tissues and skeletal muscle, which were also seen in the liver [30]. Taken together with our findings, it is suggested that insulin signaling in other pathways, including the role of other insulin-sensitive tissues such as skeletal muscles and adipose tissue, may play a role in glucose metabolism, especially in the setting of a high fructose diet.…”
Section: Discussionsupporting
confidence: 83%
“…Our research group has shown that liquid fructose supplementation in female rats fed a standard chow diet (two weeks to two months) induces glucose intolerance and IR [12,13,14,15]. However, unhealthy human dietary patterns frequently include not only excessive added sugars, but also excessive fat intake, particularly saturated fats [16].…”
Section: Introductionmentioning
confidence: 99%